Fatores de risco e proteção no desenvolvimento de transtornos mentais na gestação e pós-parto : estudo longitudinal com mulheres do interior do estado do Rio Grande do Sul - Azambuja, Carolina Viecili (2021)
The present study sought to investigate the risk and protection factors for the promotion of mental disorders during pregnancy and from pregnancy to postpartum. For this, a theoretical study was conducted and two empirical articles. Initially, the theoretical study was conducted in the literature review format, in order to identify the studies published in the area. The results showed a deficit in longitudinal studies with Brazilian samples. Next, a study was conducted with 153 pregnant women, to develop a model with outcomes and predictors through regression analysis, for the purpose of identifying risk and protective factors for mental disorders in gestation. The results pointed out different predictors for certain outcomes. Study three reassessed 97 women in the postpartum period, who had participated in the previous study, during pregnancy. Thus, it was characterized by being longitudinal and making it possible to survey risk and protection variables in this transition from pregnancy to postpartum, in relation to the promotion of mental disorders. The results mainly pointed out two factors as the most frequent among the outcomes, namely emotional abuse and the item beliefs related to the judgment of others. Finally, the last and fourth study, refers to the adaptation and validation of the Attitudes Toward Motherhood Scale for the Brazilian population. The analyzes proved to be an adequate instrument for the proposed purposes. Therefore, the set of articles in this thesis contributes to clarify the aspects involved in maternal mental disorders, specifically in the gestational and postpartum period, as well as the feasibility of using an adapted instrument that allows assessing cognitive issues, beliefs, related to maternity, for the Brazilian population. From the results, the importance of developing effective prevention and intervention programs with this population is emphasized, also aiming to minimize the impacts caused by the presence of mental disorders in women during pregnancy and the postpartum period.